Burnout and work-related stressors in gastroenterology: a protocol for a multinational observational study in the ASEAN region - John Ong; Shiaw Hooi Ho; Christopher Khor; Sharon Ong; Yock Young Dan; Wan Yen Lim; Yeong Yeh Lee; Andrew Ming Liang Ong; Xiaohui Xin; Nonthalee Pausawasdi; Mark Anthony De Lusong; Dadang Makmun; et al. (BMJ Open Gastroenterology)
Background Clinician burnout is an important occupational hazard that may be exacerbated by the novel COVID-19 pandemic. Within Southeast Asia, burnout in gastroenterology is understudied. The primary objective of this study is to estimate the prevalence of burnout symptoms within gastroenterology, in member states of the Associations of Southeast Asian Nations (ASEAN), during and after the COVID-19 pandemic. The secondary objective is to identify work-related stressors that contribute to burnout in ASEAN gastroenterologists.Methods and analysis This is an observational study that will use anonymised online surveys to estimate the prevalence of burnout symptoms at two time points: during the COVID-19 pandemic in 2020 and in 2022 (assumed to be after the pandemic). Gastroenterologists from Singapore, Malaysia, Thailand, Indonesia, Philippines and Brunei will be invited to participate in the online survey through their national gastroenterology and endoscopy societies. Burnout will be assessed using the Maslach Burnout Inventory-Human Services Survey tool. Supplementary questions will collect demographic and qualitative data. Associations between demographic characteristics and burnout will be tested by multiple regression.Results The prevalence of burnout symptoms in gastroenterology during the COVID-19 pandemic, and the baseline prevalence after COVID-19, will be established in the above-mentioned countries. Work-related stressors commonly associated with burnout will be identified, allowing the introduction of preventative measures to reduce burnout in the future.Ethics and dissemination Ethical approval was granted by the Singhealth Centralised Institutional Review Board (2020/2709). Results will be submitted for publication.